Pemeriksaan Skrining dan Edukasi Kesehatan Mental pada Lansia di Arama Kebun Kesadaran Kolongan - Munayang, Herdy; Masengi, Angelina Stevany Regina; Pali, Cicilia (Jurnal Lentera Sehat Indonesia, 2026)
The understanding of elderly and temple administrators regarding the difference between normal emotional changes due to aging and mental disorders requires attention. Using the Training Management Cycle method (assessment, design, implementation, and evaluation), the team screened 15 elderly residents using the SRQ-29 and GDS-15 instruments and provided them with progressive muscle relaxation training. The screening results indicated that some elderly residents experienced symptoms of anxiety, mild depression, and even PTSD. Despite this, all participants successfully mastered the relaxation techniques independently. In conclusion, routine screening in places of worship communities is highly effective in detecting mental health issues that are often not visible from the outside.